Collacyclumines A–D from the endophytic fungus Colletotrichum salsolae SCSIO 41021 isolated from the mangrove Kandelia candel. (March 2020) - Lin, Xiuping; Ai, Wen; Li, Meng; Zhou, Xuefeng; Liao, Shengrong; Wang, Junfeng; Liu, Juan; Yang, Bin; Liu, Yonghong
Abstract: Four undescribed alkaloids, namely collacyclumines A–D, along with a known analogue, agrocybenine, were isolated from the endophytic fungus Colletotrichum salsolae SCSIO 41021 derived from the mangrove plant Kandelia candel (L.) Druce. Collacyclumine A represents the first case of dimeric pyrrolidine alkaloid in nature. The structures of these compounds were elucidated by a combination of NMR spectra, HRESIMS data, and X-ray diffraction experiment. A proposed biosynthetic pathway of these isolated compounds were also discussed. None of compounds showed cytotoxic effects against ten cell lines. Graphical abstract: Image 1 Highlights: Collacyclumine A is the first example of a dimeric pyrrolidine alkaloid, and was confirmed by X-ray diffraction data. A proposed biosynthetic pathway was also discussed.